2017
DOI: 10.1016/j.virol.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus UL128 homolog mutants that form a pentameric complex produce virus with impaired epithelial and trophoblast cell tropism and altered pathogenicity in the guinea pig

Abstract: Guinea pig cytomegalovirus (GPCMV) encodes a homolog pentameric complex (PC) for specific cell tropism and congenital infection. In human cytomegalovirus, the PC is an important antibody neutralizing target and GPCMV studies will aid in the development of intervention strategies. Deletion mutants of the C-terminal domains of unique PC proteins (UL128, UL130 and UL131 homologs) were unable to form a PC in separate transient expression assays. Minor modifications to the UL128 homolog (GP129) C-terminal domain en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 104 publications
0
35
0
Order By: Relevance
“…GPCMV TAMYC strain infection of REPI cells was verified by immunohistochemical (IHC) staining of infected monolayers for gB viral protein at 4 days post infection ( Figure 2 i, panels A–B). TAMYC strain virus easily replicates on other non-fibroblast cell lines established in the laboratory similar to 22122 strain, including trophoblast and amniotic sac cell lines [ 18 , 19 ] (data not shown). TAMYC strain virus growth on REPI cells was highly cell-associated with very little cell-released virus ( Figure 2 ii) in contrast to 22122 strain which was 50% cell-associated and 50% cell-released virus in REPI-derived virus from infected wells of a six-well plate [ 19 ] ( Figure 2 iii).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…GPCMV TAMYC strain infection of REPI cells was verified by immunohistochemical (IHC) staining of infected monolayers for gB viral protein at 4 days post infection ( Figure 2 i, panels A–B). TAMYC strain virus easily replicates on other non-fibroblast cell lines established in the laboratory similar to 22122 strain, including trophoblast and amniotic sac cell lines [ 18 , 19 ] (data not shown). TAMYC strain virus growth on REPI cells was highly cell-associated with very little cell-released virus ( Figure 2 ii) in contrast to 22122 strain which was 50% cell-associated and 50% cell-released virus in REPI-derived virus from infected wells of a six-well plate [ 19 ] ( Figure 2 iii).…”
Section: Resultsmentioning
confidence: 94%
“…However, the model is not without specific shortcomings including reagents and assays. We have developed a number of novel cell lines and assays to enable evaluation of virus tropism and host immune responses [ 15 , 16 , 18 , 19 , 20 , 25 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the GPCMV PC appears to play a critical role in entry into many, diverse cell types, since a GP129-133 deletion mutant demonstrates defects in both endothelial cell and fibroblast cell entry [38]. The GPCMV PC, in particular the GP129, also plays a role in macrophage-mediated dissemination of virus in vivo [59], possibly mediated through a putative CC chemokine function [54]. The GPCMV PC is also required for pathogenesis in experimentally challenged, non-pregnant animals [60].…”
Section: Discussionmentioning
confidence: 99%
“…Although GP131 and GP129 were not identified by mass spectrometry analysis, we were able to observe them via western blot analysis. Furthermore, it has been suggested that GP133 will not complex with the gH/gL heterodimer in the absence of the GP131 and GP129, due, in part, to the requirement of the C-terminus of GP131 and GP133 [54], although subcomplex formation cannot be ruled out [38]. Therefore, these results indirectly suggest that there is formation of a gpPC complex when these ORFs are expressed in the MVA vectored vaccine construct.…”
Section: Expression Of Gpcmv Pc Subunits In Mvamentioning
confidence: 91%